Unmasked inside Antifa's radical plan to destroy democracy - Andy Ngo (New York Center Street, 2021)
When Andy Ngo was attacked in the streets by antifa in the summer of 2019, most people assumed it was an isolated incident. But those who'd been following Ngo's reporting in outlets like the New York Post and Quillette knew that the attack was only the latest in a long line of crimes perpetrated by antifa.
Includes bibliographical references (pages 241-294) and index
Keywords: Fascism--United States